Emotional labor and coping strategies of gynecological nurses in recurrent pregnancy loss care: a qualitative phenomenological study - Fang Yang; Dandan Liu; Guangrui Fan (BMC Nursing)
Abstract Background Recurrent pregnancy loss (RPL) is marked by multiple pregnancy losses, placing intense emotional and clinical demands on gynecological nurses who often serve as both medical and emotional support for affected patients. While prior research on emotional labor in healthcare underscores the toll of caring for bereaved individuals, few studies have examined the unique, cyclical nature of grief inherent in RPL care. Methods A qualitative, phenomenological design was employed to explore the experiences of 12 gynecological nurses working in early pregnancy units. Semi-structured interviews investigated nurses’ perceptions of emotional labor, the coping strategies they utilized, and the influence of organizational factors on their well-being. Thematic analysis guided by Braun and Clarke’s framework illuminated emerging patterns, with member checking and peer debriefing ensuring analytical rigor. Results Four key themes emerged. First, The Emotional Burden of Recurrent Loss highlighted nurses’ cumulative grief and sense of “compounding sorrow” as they supported patients through multiple losses. Second, Balancing Empathy and Professional Boundaries underscored the tension between offering genuine compassion and guarding personal emotional reserves. Third, Coping Strategies and Resilience-Building revealed a multilayered approach comprising reflective practices, peer debriefing, and self-care. Finally, Organizational Support and Gaps emphasized how institutional resources, staffing levels, and specialized training significantly shaped nurses’ capacity to sustain empathetic care. Conclusion Nurses caring for RPL patients experience heightened emotional labor due to repetitive, distressing encounters with loss. While individual and peer-based coping mechanisms foster resilience, organizational support—such as formal debriefing sessions and RPL-focused training—amplifies nurses’ well-being and ensures sustainable, high-quality care. These findings underscore the need for targeted interventions that address both the individual and systemic dimensions of emotional labor in RPL settings.